Collusion and reciprocity in infinitely repeated games - Santos-Pinto, Luís (2014)
This paper extends the standard industrial organization models of repeated interaction between firms by incorporating preferences for reciprocity. A reciprocal firm responds to unkind behavior of rivals with unkind actions (destructive reciprocity), while at the same time, it responds to kind behavior of rivals with kind actions (constructive reciprocity). The main finding of the paper is that, for plausible perceptions of fairness, preferences for reciprocity facilitate collusion in infinitely repeated market games, that is, the critical discount rate at wish collusion can be sustained tends to be lower when firms have preferences for reciprocity than when firms are selfish. The paper also finds that the best collusive outcome that can be sustained in the infinitely repeated Cournot game with reciprocal firms is worse for consumers than the best collusive outcome that can be sustained in the infinitely repeated Cournot game with selfish firms.